Effect of side wind on the directional stability and aerodynamics of a hybrid buoyant aircraft - UlHaque, Anwar; Asrar, Waqar; Omar, Ashraf Ali; Sulaeman, Erwin; Ali, JS Mohamed (EDP Sciences, 2016)
Directional stability characteristics explain the capabilities of a hybrid buoyant aircraft’s performance against the side wind, which induces flow separation that is chaotic in nature and may lead to oscillations of the aerodynamic surfaces. A numerical study is carried out to estimate the effect of side wind. The boundary conditions for the computational domain are set to velocity inlet and pressure outlet. Due to the incompressible flow at the cruise velocity, the density is taken to be constant. For these steady state simulations, the time is discretized in first order implicit and the SIMPLE scheme is employed for pressure velocity coupling alongwith k-ω SST model. Based on the results obtained so far, it is concluded that voluminous hybrid lifting fuselage is the major cause of directional.